2015
DOI: 10.1017/s0029665115003675
|View full text |Cite
|
Sign up to set email alerts
|

An investigation in the quality of diet and adequacy of energy and macronutrient intake amongst male and female university students

Abstract: Previous studies have indicated university students are often exposed to stress, lack of time and financial constraints, adversely influencing nutrient intake and status (1) . Excessive calorie intake, high dietary fat intake, alcohol and fast food consumption are commonly seen in this population, compromising an optimum nutritional status (2) .The purpose of this study was to investigate quality of diet and the adequacy of energy and macronutrient intake in university students by comparing their current nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…These poor dietary habits have been associated with the transition to independence, stress, academic and peer pressure, and taking responsibility for food choice when starting to study at university [ 3 5 ]. Several studies have reported that university students fail to meet the dietary guidelines [ 6 8 ] and gain weight in the university years [ 9 12 ], which can have adverse health consequences leading to an increased risk of obesity, type 2 diabetes, and cardiovascular diseases in later life [ 13 , 14 ]. The existence of metabolic syndrome (MetS) in young adults can be a predictor of these chronic conditions in older adults [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These poor dietary habits have been associated with the transition to independence, stress, academic and peer pressure, and taking responsibility for food choice when starting to study at university [ 3 5 ]. Several studies have reported that university students fail to meet the dietary guidelines [ 6 8 ] and gain weight in the university years [ 9 12 ], which can have adverse health consequences leading to an increased risk of obesity, type 2 diabetes, and cardiovascular diseases in later life [ 13 , 14 ]. The existence of metabolic syndrome (MetS) in young adults can be a predictor of these chronic conditions in older adults [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few strengths for this study. First of all, with regard to originality and contribution to the body of knowledge, while there are several previous studies examining nutrition (e.g., [ 8 , 49 , 50 , 51 , 52 , 53 , 54 ]) and health (e.g., [ 55 , 56 , 57 , 58 , 59 , 60 ]) of young adults, the majority of these studies use a quantitative approach to describe or quantify the issue, and a few well-conducted qualitative studies (e.g., [ 33 , 61 , 62 , 63 ]) are not focused on eating habits of the Dietetic students, as the future health care professionals. Our study explores the ‘how’ and ‘why’ questions of the eating behaviour of the Dietetic students using a qualitative approach to address the gap in our understanding in the food choice of the Dietetic students.…”
Section: Discussionmentioning
confidence: 99%
“…Original Article the nutritional attitudes of university students found that increased consumption of processed foods high in sugar, energy, and fat and a decrease in fruit-vegetable and wholegrain consumption in this population (7,8). This change in nutritional patterns may result in the triggering of hedonic appetite and hedonic hunger mechanisms.…”
Section: Hedonic Hunger On Nutrition Changementioning
confidence: 99%